2015
DOI: 10.1177/0011000015575394
|View full text |Cite
|
Sign up to set email alerts
|

Adult Attachment Dimensions and College Student Distress

Abstract: The present investigation examined dispositional hope as a psychological strength that mediates the associations between adult attachment dimensions and seven commonly assessed college student psychological symptoms, as measured by the Counseling Center Assessment of Psychological Symptoms-62 (CCAPS-62): depression, eating concerns, substance use, generalized anxiety, hostility, social anxiety, and academic distress. Structural equation modeling of data obtained from students at a large Midwestern university (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 61 publications
1
13
0
1
Order By: Relevance
“…No association was observed between infant attachment and adult social anxiety, though research has suggested this relationship may be attenuated by environment and interactions influencing attachment throughout life (Fraley et al, 2013). Additionally, lower associations between parental attachment and social anxiety in young adults (Anhalt & Morris, 2008) compared with studies measuring peer or romantic attachment (Eng et al, 2001;McDermott et al, 2015) suggest that parental attachment may contribute less to adult social anxiety. Future research would benefit from prospective designs, especially those designed to test the role of mediators between attachment and social anxiety.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…No association was observed between infant attachment and adult social anxiety, though research has suggested this relationship may be attenuated by environment and interactions influencing attachment throughout life (Fraley et al, 2013). Additionally, lower associations between parental attachment and social anxiety in young adults (Anhalt & Morris, 2008) compared with studies measuring peer or romantic attachment (Eng et al, 2001;McDermott et al, 2015) suggest that parental attachment may contribute less to adult social anxiety. Future research would benefit from prospective designs, especially those designed to test the role of mediators between attachment and social anxiety.…”
Section: Discussionmentioning
confidence: 95%
“…Nine cross-sectional studies tested indirect effects wherein the relationship between attachment and social anxiety was mediated by other variables. Significant indirect effects were reported with mediators including cognitive flexibility (Dağ & Gülüm, 2013), depression (Gajwani et al, 2013), social comparison, submissive behaviour (Aderka et al, 2009), locus of control, repetitive thinking (Gülüm & Dağ, 2013), hope (McDermott et al, 2015), social approach motivation and social avoidance motivation (Nikitin & Freund, 2010), and perceived social support (Roring, 2008). The association or overlap between these potential mediators was not fully assessed, however.…”
Section: Moderation and Mediationmentioning
confidence: 99%
“…E xtraversion and family functioning were found to mediate between insecure attachment and eating symptoms in women with ED, the total effect explained by the indirect effect was 43% and 66% respectively [62]. Furthermore, the proportion of the total effect that was explained by the indirect effect of other mediating variables such as hope and specific psychological ED traits were 21% and 37% in non-clinical mixed and female samples [48,50].…”
Section: Resultsmentioning
confidence: 99%
“…Os achados evidenciaram que a agência deve ser foco de intervenções com estudantes universitários, pois pode auxiliar no desenvolvimento de carreira dos mesmos no contexto acadêmico e nas mudanças e transições de carreira (Sung et al, 2013). Desenvolver aspectos relacionados à agência pode auxiliar a diminuir a insegurança nas tomadas de decisões (Mc Dermott et al, 2015).…”
Section: Variáveis Estudadas E Principais Resultadosunclassified